Discovery of a seismosaurus in Ecuador - Mendoza García, Luis Aníbal (Revista Universidad de Guayaquil, 1988)
In the territory that today includes Ecuador, in the sector of the Santa Elena peninsula, as in the Amazon region and very probably also in the subtropical floor of the Andes Mountains, gigantic mammals lived that formed extensive colonies, now buried in deep layers inside the earth. Due to their antiquity, there are still not enough vestiges in each of these regions and it makes a clear measurement of time impossible to establish their origin and survival.